Characterization of the start-up of single and two-stage Anammox processes with real low-strength wastewater treatment. (April 2020) - Wu, Peng; Zhang, Xingxing; Wang, Xinzhu; Wang, Chaochao; Faustin, Fangnigbe; Liu, Wenru
Abstract: In order to promote the application of anaerobic ammonium oxidation (Anammox) for municipal wastewater treatment, single and two-stage Anammox processes were started up for real low-strength wastewater treatment under similar conditions for the comparison. Results showed that the anaerobic baffled reactor (ABR)-Nitritation-Anammox and the ABR-Completely Autotrophic Nitrogen removal Over Nitrite (CANON) process took 75 days and 101 days to start up with a total nitrogen removal rate of 86–92% and 81–87% under steady state, respectively. The 16 S rRNA sequencing analysis revealed that the phylum of Proteobacteria dominated in CANON system and Anammox system with the relative abundance of 35.39% and 15.27%, respectively. Phylogenetic analysis showed that Anammox species, related to Ca. Brocadia Sinica JPN1 and Ca. Kuenenia stuttgartiensis, dominated in these two systems, respectively. The nitrogen removal performance of two-stage process was 5% higher than that of single stage process, while the start-up period and dominated Anammox species were different. Graphical abstract: Image 1 Highlights: The single and two-stages were not adversely affected by the presence of COD. Two stage process has better performance than single stage process. Proteobacteria phylum in the CANON system was more than that in the Anammox system. Ca. Kuenenia stuttgartiensis and Ca. Brocadia Sinica JPN1 dominated differently.